Answer:
-2y + 3 = 0
Step-by-step explanation:
x - 6y - 9 = 0
-6y - 9 = -x subtract x from both sides
6y + 9 = x divide both sides by -1
x = 8y + 6
6y + 9 = 8y + 6 replace x with 6y + 9
-2y + 9 = 6 subtract 8y from both sides
-2y + 3 = 0 subtract 6 from both sides
Answer:
3x+12
Step-by-step explanation:
You need to do 3 times x which equals 3x and then do 3 times 4 and get 12 so it ends up as 3x+12
hope this helps
stay safe:)))
brainliest is appreciated
this person keeps copying and reporting my questions and then saying i copied them so im sorry if that happens :(
Answer:
2.408
Step-by-step explanation:
Answer:
carly used 1 1/4 cups of lemonade
Step-by-step explanation:
I think that is simplified
Answer:
Hence, Grasshopper will land on the ground after 1.5 sec.
Step-by-step explanation:
It s given that:
The height, in feet, of the grasshopper above the ground after t seconds is modeled by the function:
![h(t)=-t^2+\dfrac{4}{3}t+\dfrac{1}{4}](https://tex.z-dn.net/?f=h%28t%29%3D-t%5E2%2B%5Cdfrac%7B4%7D%7B3%7Dt%2B%5Cdfrac%7B1%7D%7B4%7D)
Now we are asked to find:
In how many seconds will the grasshopper land on the ground?
i.e. we have to find the value of t such that h(t)=0
i.e.
![-t^2+\dfrac{4}{3}t+\dfrac{1}{4}=0](https://tex.z-dn.net/?f=-t%5E2%2B%5Cdfrac%7B4%7D%7B3%7Dt%2B%5Cdfrac%7B1%7D%7B4%7D%3D0)
i.e. we need to find the roots of the given quadratic equation.
On solving the quadratic equation or plotting it's graph we could observe that the point where h(t)=0 are:
![t=-\dfrac{1}{6},t=\dfrac{3}{2}](https://tex.z-dn.net/?f=t%3D-%5Cdfrac%7B1%7D%7B6%7D%2Ct%3D%5Cdfrac%7B3%7D%7B2%7D)
As time can't be negative hence we will consider:
![t=\dfrac{3}{2}=1.5sec](https://tex.z-dn.net/?f=t%3D%5Cdfrac%7B3%7D%7B2%7D%3D1.5sec)
Hence, grasshopper will land on the ground after 1.5 sec.